2004
DOI: 10.1051/0004-6361:20040118
|View full text |Cite
|
Sign up to set email alerts
|

VLTI/VINCI observations of the nucleus of NGC 1068 using the adaptive optics system MACAO

Abstract: Abstract. We present the first near-infrared K-band long-baseline interferometric measurement of the nucleus of the prototype Seyfert 2 Galaxy NGC 1068 with resolution λ/B ∼ 10 mas obtained with the Very Large Telescope Interferometer (VLTI) and the two 8.2 m diameter Unit Telescopes UT 2 and UT 3. The adaptive optics system MACAO (Multi Application Curvature Adaptive Optics) was employed to deliver wavefront-corrected beams to the K-band commissioning instrument VINCI. A squared visibility amplitude of 16.3 ±… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
99
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
4
2

Relationship

3
7

Authors

Journals

citations
Cited by 99 publications
(107 citation statements)
references
References 30 publications
7
99
1
Order By: Relevance
“…Over the last few years, using AO for NIR observations, it has become possible to probe these objects at 100mas scales. MIR interferometry has now resolved the dusty torus for ~10 AGN and even more detailed views were possible for NGC 1068 [23], [24] and NGC 4151 [25]. GRAVITY will continue that route to smaller angular sizes.…”
Section: Active Galactic Nucleimentioning
confidence: 97%
“…Over the last few years, using AO for NIR observations, it has become possible to probe these objects at 100mas scales. MIR interferometry has now resolved the dusty torus for ~10 AGN and even more detailed views were possible for NGC 1068 [23], [24] and NGC 4151 [25]. GRAVITY will continue that route to smaller angular sizes.…”
Section: Active Galactic Nucleimentioning
confidence: 97%
“…The most promising tool for this task is IR interferometry, which was already successfully used for a number of nearby objects (Swain et al 2003;Wittkowski et al 2004;Weigelt et al 2004;Jaffe et al 2004;Poncelet et al 2006;Meisenheimer et al 2007;Tristram et al 2007Tristram et al , 2009Beckert et al 2008;Raban et al 2009;Burtscher et al 2009;Kishimoto et al 2009b). However, except for reconstructed images of NGC 1068 obtained from Speckle interferometry (Weigelt et al 2004), long-baseline interferometry usually provides spatial information coded as Fourier space observables, i.e.…”
Section: Interferometry Of Dust Torimentioning
confidence: 99%
“…Speckle imaging from the Keck Observatory also showed that the flux emitted by the core of the AGN may be accounted for by an unresolved point source whose size is smaller than ∼20 mas and which is surrounded by an emitting region extending up to 10 pc (Weinberger et al 1999). Wittkowski et al (2004) combined near-IR speckle data with the K-band visibility point obtained with VINCI and interpreted the whole dataset with a two-component model: a small one having a size of ∼5 mas (or 0.4 pc) responsible for 40% of the K-band flux and an extended one of ∼40 mas. In addition, near-IR bispectrum speckle interferometric observations led to a N-W extended structure in K -band having a size of 39×18 mas and a PA ∼ −16 • (Weigelt et al 2004).…”
Section: Spatial Description Of the Sourcementioning
confidence: 99%